Data processing center of RadioAstron space VLBI project. Issue 2 (15th January 2020) - Shatskaya, M.V.; Abramov, A.A.; Fedorov, N.A.; Kostenko, V.I.; Likhachev, S.F.; Seliverstov, S.I.; Sychev, D.A.
Abstract: In this paper, questions on development, implementation, and operation of RadioAstron project Data Processing Center (DPC) are reviewed. The main components of the dedicated DPC are the computer complex with 1 TFlops/s performance, storage with memory capacity of approximately 10 PB, the network infrastructure, and the corresponding communication channels. Performance enhancement methods and resolution of information storage, archiving, and process problems of space VLBI high-speed digital data flows are analyzed. It is shown that successful operation of DPC is mainly provided by optimal organization of computer system structure, storage, and networking transmission. Some of the important key features of RadioAstron project DPC and its comparative differences from the standard VLBI procedures are considered.